Detecção do vírus da anemia infecciosa das galinhas em Minas Gerais - Priscilla Rochele Barrios (2009)
A wide range study was conducted on chicken anemia virus (CAV) in order to investigate the occurrence of CAV in different chicken populations and potential sources of infection. Tissue and biological samples were studied by nested PCR and sequencing, including thirty-two industrial chickens, twenty subsistence chickens, twenty-eight commercial poultry live and inactivated vaccines and sixteen birds of the avian fauna. The fourteen CAV amplicons sequenced included materials from the poultry industry (7), from subsistence chickens (4), from vaccines (2) and from the avian fauna (1). The genetic characterization by variation analyses of the VP2 and VP3 coding regions sequences were compared to sequence data deposited in the GenBank. The nucleotide and deducted amino acid sequences were aligned to the Cuxhaven-1 (Cux-1) prototype strain sequences for comparisons. The phylogenetic analyses of local CAV indicated high similarity of sequences irrespective of source, as well as to CAV sequences published for strains in all continents, although discrete as compared to Cux-1. However, the nucleotide substitutions did not result in amino acid change, except for the VP2 153 position, in which a change from alanine to valine was deducted. CAV was detected in five (5/28; 18%) vaccines produced between 1991 and 1996, including embryo (Newcastle and avian encephalomyelitis) and fibroblast monolayer (Marek's disease) vaccine viruses, but in none produced in the present decade. The detection of CAV in five batches of commercial vaccines of three different major laboratories may be considered an important factor for the present high CAV dissemination. In the subsistence chickens of the metropolitan region of Belo Horizonte, CAV genome was detected in (6/20; 33%). CAV may be of importance for the free-range chickens, although not as yet evaluated, for its potential immunosuppressive impact. CAV infection in free-range chickens may have also epidemiological importance, as additional source and risk for industrial chickens. Although the original source to free-range chickens might have been the industrial chickens infected, vaccinated with CAV vaccines or given CAV-contaminated vaccines, as indicated by the genetic similarity of strains, native free-range strains might also occur